Relationship Among Mothers' Glycemic Level, Periodontitis, and Birth Weight. Issue 3 (1st March 2016) - Gomes‐Filho, Isaac S.; Pereira, Eliesita C.; Cruz, Simone S.; Adan, Luis Fernando F.; Vianna, Maria Isabel P.; Passos‐Soares, Johelle S.; Trindade, Soraya C.; Oliveira, Ernesto P.; Oliveira, Michelle T.; Cerqueira, Eneida de M. M.; Pereira, Antonio Luis; Barreto, Maurício L.; et al.
Abstract : Background: The aim of this study is to determine the influence of glycemic level on the relationship between periodontitis and low birth weight (LBW). Methods: A case‐control study was conducted with 372 females divided into cases (109 mothers of newborns with birth weight <2, 500 g) and controls (263 mothers of newborns with birth weight ≥2, 500 g). The birth weight of children was obtained from medical records, whereas information on sociodemographic, lifestyle, and health characteristics of the participants was obtained through an interview. Glycated hemoglobin (HbA1c) levels were measured, and probing depth, clinical attachment levels, and bleeding on probing were used to determine the periodontal status. Results were analyzed using logistic regression. Results: The likelihood of having children with LBW among the mothers with periodontitis was six times greater than that observed among mothers without periodontitis (adjusted odds ratio [ORadjusted ] = 6.02, 95% confidence interval [CI] = 2.47 to 15.17), even after adjustment. There was also a strong, statistically significant relationship between periodontitis and LBW in both the normal glycemic–level group (HbA1c levels <5.6%, unadjusted odds ratio [ORunadjusted ] = 8.30, 95% CI = 3.56 to 19.35) and the high glycemic–level group (HbA1c levels ≥5.6% and <6.5%, ORunadjusted = 5.73, 95% CI = 1.75 to 18.70). After adjustment for confounders, the magnitude of the association continued to be strong in the normal glycemic–level group (ORadjusted = 7.59, 95% CI = 2.7 to 24.28), an increase of 25% when compared to the main association measurement. In those with high glycemic levels (ORadjusted = 4.03, 95% CI = 0.81 to 19.96), the OR decreased almost 50%, and the association lost statistical significance. Conclusion: Periodontitis and glycemic levels appeared to have opposing influences on birth weight, with periodontitis being associated with LBW and the magnitude of the association being altered depending on maternal blood glucose level.